Understanding Residential Needs of Single or 2-Resident Households with a Focus on Communal Amenities of Multi-Family Housing Complexes. Issue 2 (1st May 2016) - Lee, Sang Ho; Lee, Eunjoo
Abstract: Due to rapid socio-demographic changes in Korean society, the number of single or 2-resident households i.e. small households, are increasing at a faster rate than expected. This research aimed to achieve a clear understanding of the residential needs of small households, which are distinctively different from those of regular households created by blood relations. A survey was carried out to identify the general residential needs of small households, and their communal amenity needs. It was found that small households had clearly different residential needs compared to regular households; the needs were generally uniform among regular households, while small households showed significant differences according to socio-demographics, residential conditions, lifestyle and continuation period of households. Given this, small households were categorized into four subgroups and characterized by type, according to the specific residential needs and communal amenity needs of each subgroup. As a result, this research was able to empirically embrace previous researches, which were sporadically carried out on some subgroups of small households, and to formulate residential conditions that the residents of small households want, based on the understanding of their residential needs rather than simple socio-demographic characteristics.